STRATEGY FOR MICRO, SMALL AND MEDIUM BUSINESS DEVELOPMENT STRATEGIES ECONOMY IN COASTAL COMMUNITIES (Case Study on Shrimp Sambal Business in Lamongan District) - Wahyu Endriyanto; Sutikno Wahyu Hidayat; Faiq Mumtaz M (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2019)
This study aims to determine the development strategy of Micro, Small and Medium Enterprises (UMKM) in strengthening the populist economy of coastal communities in shrimp sauce business in Lamongan Regency. The approach used in this study is a qualitative approach. The subject of the research is the shrimp chili business owner in Lamongan Regency. The data analysis techniques used are qualitative analysis techniques and SWOT analysis. Where qualitative analysis uses triangulation data collection techniques while SWOT analysis is used to identify various factors systematically and formulate a company's strategy. The results of this study indicate that the strategy of developing small businesses in strengthening the people's economy in the shrimp chilli business in Lamongan Regency that can be used is the development of markets and products, as well as intensive market penetration by increasing promotion, quality, and innovation of marine products of Lamongan Regency.Keywords: Development strategy, strengthening people's economy, UMKM.